Global, regional, and national burden of diabetes from 1990 to 2021, with projections of prevalence to 2050: a systematic analysis for the Global Burden of Disease Study 2021 - Kanyin Liane Ong; Lauryn K. Stafford; Susan A. McLaughlin; Edward J. Boyko; Stein Emil Vollset; Amanda E. Smith; Bronte E. Dalton; Joe Duprey; Jessica A. Cruz; Hailey Hagins; Paulina A. Lindstedt; Darshan B. B.; et al. (The Lancet, 2023)
Diabetes is one of the leading causes of death and disability worldwide, and affects people regardless of country, age group, or sex. Using the most recent evidentiary and analytical framework from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD), we produced location-specific, age-specific, and sex-specific estimates of diabetes prevalence and burden from 1990 to 2021, the proportion of type 1 and type 2 diabetes in 2021, the proportion of the type 2 diabetes burden attributable to selected risk factors, and projections of diabetes prevalence through 2050.
Keywords: 330